2013
DOI: 10.1186/1471-2334-13-564
|View full text |Cite
|
Sign up to set email alerts
|

HPV clearance in postpartum period of HIV-positive and negative women: a prospective follow-up study

Abstract: BackgroundHPV persistence is a key determinant of cervical carcinogenesis. The influence of postpartum on HPV clearance has been debated. This study aimed to assess HPV clearance in later pregnancy and postpartum among HIV-positive and negative women.MethodsWe conducted a follow-up study with 151 HPV-positive women coinfected with HIV, in 2007–2010. After baseline assessment, all women were retested for HPV infection using PCR in later pregnancy and after delivery. Multivariable logistic regressions assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
16
1
1
Order By: Relevance
“…The clearance rates observed in our study was significantly lower than reported in studies (68.3 to 80.7%) among HIV-seronegative women. 4,2225 However previous studies amongst HIV-seropositive women have reported HPV clearance rates that are comparable 16 , higher 4,8,23,26 and even lower 19 than ours. As reported in earlier studies, we too observed lower clearance rates in women having infection with carcinogenic HPV types especially the alpha-9 species, compared to the clearance rate among carcinogenic HPV types.…”
Section: Discussioncontrasting
confidence: 65%
“…The clearance rates observed in our study was significantly lower than reported in studies (68.3 to 80.7%) among HIV-seronegative women. 4,2225 However previous studies amongst HIV-seropositive women have reported HPV clearance rates that are comparable 16 , higher 4,8,23,26 and even lower 19 than ours. As reported in earlier studies, we too observed lower clearance rates in women having infection with carcinogenic HPV types especially the alpha-9 species, compared to the clearance rate among carcinogenic HPV types.…”
Section: Discussioncontrasting
confidence: 65%
“…The most prevalent HPV genotypes were LR-HPV, including HPV-6 and -11, followed by HR-HPV -18, -16 and -31 (Table 1). Greater elimination of HPV was observed in women infected by LR-HPV compared to HR-HPV, but this difference was not significant (Jalil et al, 2013).…”
Section: Prevalence Of Hpv and Cervical Abnormalities In Hiv+ Brazilimentioning
confidence: 75%
“…Of the 6430 potential publications identified from the PubMed and Embase searches, 55 met our inclusion criteria. Figure summarizes publication selection, Table summarizes the characteristics of the included studies, and Tables ,,, (Appendix ) describe the extracted data and their quality.…”
Section: Resultsmentioning
confidence: 99%
“…Figure summarizes publication selection, Table summarizes the characteristics of the included studies, and Tables ,,, (Appendix ) describe the extracted data and their quality. In review 1 , of the effect of HIV status (exposure) on subsequent HPV acquisition and clearance (outcomes), we extracted data from a total of 41 publications reporting on 27 independent studies . In review 2, of the effect of HPV status (exposure) on subsequent HIV acquisition (outcome), we extracted data from a total of 15 publications reporting results from 11 independent studies .…”
Section: Resultsmentioning
confidence: 99%